“Padi Lingko” to Reduce Hexavalent Chromium Levels (Cr(VI)) in Citarum River Water Sample - Aeni, Suci Rizki Nurul; Nurdin, Nurdin; Ansori, Ikhsan Faisal (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Clean water is increasingly difficult to obtain, even though water is a chemical compound that is very important for living creatures' lives. Industrial and domestic community waste are a big problem in polluting the Citarum River, causing the water to become unfit. One of the toxic heavy metals found in Citarum River water is chromium (Cr(VI)). The technique that can be used to remove the heavy metal Cr(VI) in Citarum river water samples is adsorption using biological material (biosorption). Biosorption is the process of absorbing metal ions by materials originating from nature. In this research, jengkol peel was used. A modification of this research from previous research is the design of the "Padi Lingko" tool. This research aims to determine the results of the function test of the Padi Lingko tool and measure chromium(VI) levels in treated Citarum river water samples. The results of the analysis show that the power supply measurement results are in accordance with the expected values. The speed test results show appropriate values, namely at a low speed of 213 rpm, a medium speed of 1109 rpm, and a high speed of 1225 rpm. The timer test results show the appropriate time, with an average error factor of -0.02%. The results of the storage bucket test showed that when operated, the bucket did not produce vibrations or noise and could hold water. Apart from that, there are no leaks in the collection bucket. The test results show that the drive motor works well and can rotate the shaft without stuttering. The Padi Lingko tool could be used and succeeded in reducing Cr(VI) until a final level of 0.0529 mg/L was obtained.